2006
DOI: 10.2471/blt.06.029819
|View full text |Cite
|
Sign up to set email alerts
|

The syndromic management of vaginal discharge using only single-dose treatments: a randomized controlled trial in West Africa

Abstract: Objective To evaluate whether single-dose treatments are as effective as standard therapy in the syndromic management of vaginal discharge. Methods A randomized controlled effectiveness trial compared single-dose tinidazole plus fluconazole (TF) with treatment for 7 days with metronidazole plus 3 days of treatment with vaginal clotrimazole (MC) among 1570 women presenting with vaginal discharge at primary health care institutions in Ghana, Guinea, Mali and Togo. Participants were randomly allocated to one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…The first evidence of an association came from a Japanese study, reported in 1997 (225), in which M. genitalium was detected in the cervices of 5 (9%) of 57 women with cervicitis but in none of 79 women without the condition. Subsequently, the results of other studies (2,4,11,23,48,57,80,89,137,139,148,163,165,225), shown in Fig. 5, to a large extent attest to M. genitalium having a significant role in causing cervicitis.…”
Section: Cervicitismentioning
confidence: 95%
“…The first evidence of an association came from a Japanese study, reported in 1997 (225), in which M. genitalium was detected in the cervices of 5 (9%) of 57 women with cervicitis but in none of 79 women without the condition. Subsequently, the results of other studies (2,4,11,23,48,57,80,89,137,139,148,163,165,225), shown in Fig. 5, to a large extent attest to M. genitalium having a significant role in causing cervicitis.…”
Section: Cervicitismentioning
confidence: 95%
“…Pepin and Sobela et al observed complete relief of vaginal discharge with syndromic management in 66%. 8 Bornstein et al studied effect of combination therapy versus cotrimazole therapy on vaginitis. 9 They enrolled 165 patients out of which 84 were given combination therapy and 81 were on cotrimazole therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, the prevalence of M. genitalium ranges from 2–17%, with highest prevalence among men and women with genital discharge or genital ulcers [58]. Studies in western Africa found prevalences of 2% in the general population [9]; 12–18% in HIV infected or symptomatic persons [1011]; and 26% in female sex workers [12]. In eastern Africa the prevalence of M. genitalium has been reported to be 3–5% in the general population in Tanzania [1314], 16% in female sex works in Nairobi, Kenya [15], and 17% in HIV-positive women in Mombasa, Kenya [16].…”
Section: Introductionmentioning
confidence: 99%